Pattern & Methodology of Al Khaṣāiṣ-ul-Kubra by Imām Jalāl ud Dīn Suyūṭī - Rao, Muhammad Atif Aslam; Aijaz Bashir (Journal of Islamic and Religious Studies, 2019)
Imām Jalāl-ud-Dīn Suyūtī (d.911 A.H.)– a great personality of Islām, devoted his entire life for the services of Islām. He authored a number of books on multiple disciplines of Islām. One worth-mentioning contribution of Imām Suyūtī is his book ‘Al Khaṣāiṣ al Kubra’. A number of Arab researchers have compiled analytical research works on specific topics and certain chapters of the book. However, a collective analysis on the pattern and methodology of the book is not present so far. Therefore, this article deals with a holistic and collective discussion on the approach and patterns of the book for the first time in Urdu language. The article enlightens its readers with a comprehensive introduction of the book in the beginning. However, lately, it thoroughly reviews and analyzes the style and method of Imām Jalāl-ud-Dīn Suyūtī. Moreover, the article also contains details of the significance and genuine qualities of the book along with its distinctive features. The study concludes that the worthwhile work of Imām Jalāl-ud-Dīn Suyutī in this particular field deserves to be acknowledged genuinely.